(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
A study was conducted to estimate genetic variability, correlation and direct and indirect effects of yield attributes on seed yield of fourteen Bangladeshi varieties of Brassica rapa. High heritability coupled with high genetic advance was recorded in a number of secondary branches plant-1, a number of siliqua plant-1 and a number of seeds siliqua-1 indicating the effects of additive genes in controlling the traits. Significant and positive association with seed yield plant-1 were observed in the number of primary branches plant-1, a number of seeds siliqua-1, while a negative association was found in days to maturity. The path analysis revealed that the days to first flowering, number of secondary branches plant-1 and 1000 seed weight were the main contributors to seed yield. The results suggest that days to first flowering, number of primary and secondary branches plant-1 and 1000 seed weight may be considered for selection to improve the seed yield in B. rapa. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 95-107, 2020